The Cronenberg question. Issue 2 (3rd April 2017) - Lowenstein, Adam
Abstract: This is an introduction to a special dossier of six essays devoted to the work of director David Cronenberg. The dossier, edited by Adam Lowenstein and Adam Charles Hart, is organized around 'The Cronenberg Question': What exactly do we mean when we call something 'Cronenbergian'? Most commentators use 'Cronenbergian' to signify qualities strongly associated with films like Shivers (1975), Scanners (1981), Videodrome (1983), and The Fly (1986): the disturbing, often grisly transformation of the human body through scientific technology in a spectacle commonly dubbed 'body horror'. But Cronenberg has been making films for more than 50 years and the conventional definition of 'Cronenbergian' fits only a minority of his output. So what is to be done with Cronenberg and our sense of the 'Cronenbergian' now? This dossier offers a number of strategic responses to this question, including explorations of Cronenberg's films as Jewish, anesthetic, minor, monstrous, political, and sexually violent. The ambition of the dossier is to shift our understanding of the 'Cronenbergian'.